Exposure to Violence and Beliefs About Violence Against Women Among Adolescents in Nigeria and South Africa - Sunday B. Fakunmoju; Shahana Rasool (SAGE Open, 2018)
Although adolescents’ exposure to violence and oppressive gender attitudes is prevalent, comparative knowledge across countries is sparse. This study examined exposure to intimate partner violence (IPV), family violence, and beliefs about violence against women (VAW) in a convenience sample of 2,462 adolescents from 44 schools in Nigeria and South Africa. Findings suggested that exposure to IPV, family violence, and beliefs about VAW differed by gender and country. Specifically, adolescents from Nigeria were more likely to be exposed to IPV and family violence and were more likely to endorse VAW than adolescents from South Africa. Male adolescents were more likely to endorse VAW than were female adolescents. Similarly, higher age, being male, being from Nigeria, being in a relationship, and greater exposure to family violence were associated with higher endorsement of VAW. Findings suggest that effective prevention programs are needed in both countries to mitigate exposure to IPV and family violence. Concerted efforts are also required to work with exposed adolescents to inhibit pro-VAW beliefs and stop the intergenerational transmission of violence. Additional implications of findings for policy, practice, and research are discussed.